NEW DISTRIBUTIONAL RECORD OF GERRES MACRACANTHUS BLEEKER FROM INDIAN WATERS - Venkataraman, G; Badrudeen, M (Indian Journal of Fisheries, 2011)
The occurrence of Gerres macracanthus Bleeker is recorded for the first time from Indian waters. A description of the species is given and the differences between this and the allied species, G. filamentosus, are pointed out.